Descemet-stripping automated endothelial keratoplasty with intrascleral haptic-fixated intraocular lens in a sequential vs simultaneous approach - Sinha, Rajesh; Shiny, Hannah; Nair, Sridevi; Sharma, Namrata; Agarwal, Tushar; Titiyal, Jeewan Singh (Journal of cataract and refractive surgery, 2021)
Performing DSAEK and SF IOL surgery in patients with corneal decompensation associated with aphakia or complicated pseudophakia in staged rather than simultaneous approach resulted in better anatomical and functional outcomes. Purpose:To compare the outcomes of Descemet-stripping automated endothelial keratoplasty (DSAEK) with intrascleral haptic-fixated intraocular lens (IOL) in a sequential and simultaneous approach.Setting:Tertiary eyecare center.Design:Prospective randomized comparative study.Methods:Patients with aphakic or complicated pseudophakic bullous keratopathy visiting a tertiary eyecare center were included in the study. A total of 40 patients were randomized into 2 groups of 20 each. Group 1 had subjects who underwent scleral-fixated IOL (SF IOL) implantation by intrascleral haptic fixation technique, followed by DSAEK (sequential procedure) with an interval of at least 3 months. Group 2 (simultaneous) had subjects who underwent DSAEK with SF IOL as a combined procedure. Graft survival, endothelial cell loss (ECL), corrected distance visual acuity (CDVA), and need for any intervention such as rebubbling were evaluated for both the groups at the end of 6 months.Results:At 6 months, the sequential group had significantly better CDVA of 0.62 ± 0.17 logMAR compared with 0.87 ± 0.19 logMAR in the simultaneous group (P = .002). Group 1 had significantly better overall cumulative graft survival (100% vs 60%, P = .002), significantly lower ECL (P = .006), lesser mean central corneal thickness (P = .03), and significantly thinner donor lenticule (P = .009). Rebubbling rate was significantly higher in Group 2 (P = .025). The mean hyperopic shift was significantly more in Group 2 (P = .02).Conclusion:The sequential procedure of SF IOL followed by DSAEK has better visual outcomes and graft survival when compared with simultaneous procedure in cases of aphakic or complicated pseudophakic bullous keratopathy.